Informações sobre segmentos operacionais no Brasil : práticas e determinantes de divulgação - Souza, Júlia Alves e (2013)
With business diversification, economic globalization and harmonization of international accounting standards, disclosure of information about operating segments assumes increasing importance and tends to favor the economic-financial analysis of entities. In 2009, was issued in Brazil the Pronouncement CPC 22, which directs companies on the way that should be defined their operating segments and how these data should be disclosed in the annual financial statements. In view of gaps on the analysis of financial information by segment, this study aims to identify factors that influence the level of disclosure of information about operating segments of Brazilian companies. Herewith, aims to present the practices of disseminating information about operating segments presented by these companies. The research, exploratory and explanatory, develops initially from the analysis of financial statements of companies, with reference to the requirements of CPC 22. Use also the statistical model of multiple linear regression analysis. It approached the disclosure for the years of 2010 and 2011, and 2010 was the first year of such compulsory disclosure by Brazilian public companies. The study covers 272 companies distributed across 20 economic sectors, totaling 544 statements analyzed. Regarding the disclosure practices of segments, the results indicate that there was no uniformity in the practices of such companies, as expected (given the discretion allowed by CPC 22 and the various organizational structures). Identify differences in the types of information disclosed and the same levels of detailing, both between different sectors and between firms in the same sector. It appears, also, that the level of corporate disclosure have not explored all the points mentioned in Statement (part of them even mentioned the existence of operating segments), and thus it is evident that there was not full compliance with the requirements of CPC 22. In relation to the factors that influence this disclosure, are tested hypotheses about the 8 characteristics identified as potential determinants, as Disclosure Theory, the Theory of Agency and/or previous studies that address the disclosure of segment information. For the characteristics "profitability", "sector concentration", "profit or loss" and "reporting year" are not obtained statistically significant results, indicating that these factors do not influence such disclosure levels. Is also concluded, in relation to companies analyzed: (i) the larger the company, the greater the level of disclosure about segments, (ii) the greater the degree of indebtedness of the company, the greater the level of disclosure about segments, (iii) companies listed in the Corporate Governance Levels of BM&FBOVESPA have higher levels of disclosure that companies not belonging to them, and (iv) companies audited by one of the "Big Four" have higher levels of disclosure that audited by "other companies". Thus, the results reveal that features "size", "debt", "corporate governance" and "audit" are determinants of levels of disclosure about segments of Brazilian companies.